Protection of Distal Embolization in High-Risk Patients With Acute ST-Segment Elevation Myocardial Infarction (PREMIAR) - Cura, Fernando A.; Escudero, Alejandro Garcia; Berrocal, Daniel; Mendiz, Oscar; Trivi, Marcelo S.; Fernandez, Juan; Palacios, Alejandro; Albertal, Mariano; Piraino, Ruben; Riccitelli, Miguel Angel; Gruberg, Luis; Ballarino, Miguel; et al. (The American journal of cardiology, 2007)
Distal embolization may decrease myocardial reperfusion after primary percutaneous coronary intervention (PCI). Nonetheless, results of previous trials assessing the role of distal protection during primary PCI have been controversial. The Protection of Distal Embolization in High-Risk Patients with Acute ST-Segment Elevation Myocardial Infarction Trial (PREMIAR) was a prospective, randomized, controlled study designed to evaluate the role of filter-based distal protection during PCI in patients with acute ST-segment elevation myocardial infarction at high risk of embolic events (including only baseline Thrombolysis In Myocardial Infarction grade 0 to 2 flow). The primary end point was continuous monitoring of ST-segment resolution. Secondary end points included core laboratory analysis of angiographic myocardial blush, ejection fraction measured by cardiac ultrasound, and adverse cardiac events at 6 months. From a total of 194 enrolled patients, 140 subjects were randomized to PCI with or without embolic protection, and 54 were included in a registry arm due to the presence of angiographic exclusion criteria. Baseline characteristics were comparable between arms. The rate of complete ST-segment resolution (≥70%) at 60 minutes was similar in patients treated with or without distal protection (61.2% vs 60.3%, respectively, p = 0.85). Angiographic myocardial blush (67% vs 70.7%, p = 0.73), in-hospital ejection fraction (47.4 ± 9.9% vs 45.3 ± 7.3%, p = 0.29), and combined end point of death, heart failure, or reinfarction at 6 months (14.3% vs 15.7%, p = 0.81) were consistently achieved in a similar proportion in the 2 groups. In conclusion, the use of filter-based distal protection is safe and effectively retrieves debris; however, such use does not translate into an improvement of myocardial reperfusion, left ventricular performance, or clinical outcomes.